Geochemical characterization of inorganic constituents in coalbed methane flowback water and economic evaluation of trace metal recovery - Yihua Wu; Chunyan Yang; Chaoyang Li; Yanzhang Li; Hongyi Chen; Chengyue Li; Jiayuan He; Baicang Liu (Water Research, 2026)

Construction of donkey skin fibroblast immortalized cell line and comparative analysis with primary cells - Shengye Bao; Zhihai Huang; Baosheng Liao; Danchun Zhang; Ying Sun; Xiaoxia Ding; He Su; Jiang Xu; Hongyi Li; Lu Gong (Tissue and Cell, 2026)

Genetic diversity of MHC and coccidial mitogenomes from fecal samples of the red‑crowned crane (Grus japonensis) - Wei Xu; Xinyi Zhao; Nan Xu; Ying Zhu; Keyi Tang; Ke He; Hongyi Liu (The Veterinary Journal, 2026)

Biomimetic hybrid fibers integrate scaffold topology and bioinert protein cues to harmonize microglial phagocytosis and anti-neuroinflammation - Ming Yin; Chenlong He; Yuwei Wang; Jingwen Qin; Huawei Liu; Han Zhou; Hongyi Zhang; Shan Hua; Shengming Wu; Jing Chen; Keyue Xiao; Qihui Wu; et al. (Chemical Engineering Journal, 2026)

Immunotherapy of cold tumors via full-course ICD activation by nanotherapeutics-based cascade precise tumor killing and efferocytosis inhibition - Shengming Wu; Huawei Liu; Han Zhou; Jingwen Qin; Chenlong He; Ming Yin; Hongyi Zhang; Shan Hua; Zhonghua Liu; Yilong Wang (Chemical Engineering Journal, 2026)

Evolving natural yeast to protein-rich micro-grain adaptable for non-sterile low-carbon biomanufacturing - Xinru Wang; Zhaoyu Xu; Zhihui Shi; Weihe Rong; Hailin He; Hongyi Zhou; Lu Liu; Zhijia Liu; Wenjie Sui; Guokun Wang; Yanhe Ma (Bioresource Technology, 2026)

Integrative multi-omics and machine learning reveal glycolysis-related biomarkers driving vascular remodeling in pulmonary arterial hypertension - Hongyi Tian; Zihua Liu; Junrui He; Ruyuan Wei; Xiao Bai; Kai Liu (Molecular and Cellular Biochemistry, 2026)

MnO2-functionalized membrane with enhanced demulsification and antifouling performance for stable oil-in-water emulsion separation - Sudong Yang; Zhiying He; Mei Zhu; Junjie Zheng; Yixuan Kuang; Hongyi Li; Xueting Yuan; Qing Xu; Qian Zhang; Peng Zhao; Jianmin Luo; Lin Chen (Journal of Environmental Chemical Engineering, 2026)

DNMT1-mediated LAMA2 inhibition induces M2 macrophage polarization during prostate cancer progression - Ruiqian Li; Chen Hu; Fengming Ran; Yu Bai; Hongyi Wu; Wenjun Peng; Yixuan He; Qilin Wang; Jun Li (Tissue and Cell, 2026)

What are the policy effects of implementing a national strategic plan pertaining to territorial functional zoning? An empirical study from Sichuan province - Qiong Xian; Meng Yuan; Chao Yang; Qiyan Huang; Yanmei He; Hongyi Pan (Journal of Geographical Sciences, 2026)

A solution method for hydrodynamic coefficients of autonomous underwater vehicle using multi-degree-of-freedom coupled motion data - Xinxin Wei; Hongyi Du; Tianhong Yan; Bo He (Ocean Engineering, 2025)

Vibration control of large-scale pipelines in propane dehydrogenation units based on eddy current tuned mass damper - Jia He; Haohua Liang; Yuqiang Yang; Zhibo Guo; Deyu Li; Hongyi Zhang; Xugang Hua; Zhengqing Chen (Engineering Structures, 2025)

Mechanisms driving spectral properties and their associations with above-ground biomass dynamics in a temperate forest - Pengcheng Jiang; Han He; Zikun Mao; Yanjun Su; Mengxu Zhang; Zhichao Xu; Meihui Zhu; Jin Yin; Hongyi Jiang; Shuai Fang; Xugao Wang (Forest Ecology and Management, 2025)

Unveiling the vertical dynamics of atmospheric ammonium in Asia megacity: A GRASP-based investigation of spatiotemporal patterns and source drivers - Yining Tan; Ting Yang; Hongyi Li; Ping Tian; Yifan Song; Jiancun He; Yutong Tian; Yele Sun; Zifa Wang (Atmospheric Research, 2025)

Sulfophilic metal ions in groundwater induce particle structure and dechlorination efficiency change of sulfidated zero-valent iron - Shichao Cai; Yurou Tan; Hongyi Li; Bo Chen; Feng He (Water Research, 2025)

Elevational variation in leaf anatomical and stomatal traits and their allometric relationships of Quercus variabilis from a warm-temperate forest - Huifang Zhang; Yang Liu; Siyuan Huangfu; Baixue Zhang; Haoqin Ma; Huinan Ma; Jingjing Wang; Haibo Li; Hongyi He; Yu Wang; Houjuan Song; Xiuqing Yang (Photosynthesis Research, 2025)

Spatial distribution of mercury in geothermal springs and its correlation with tectonic setting in the Bayan Har block of Tibetan Plateau, China - Ke Zhang; Hongyi He; Ying Li; Chang Lu; Zihan Gao; Zhaofei Liu; Zhi Chen (Geothermics, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Unveiling the intricate dynamics of PM2.5 sulfate aerosols in the urban boundary layer: A pioneering two-year vertical profiling and machine learning-enhanced analysis in global Mega-City - Hongyi Li; Ting Yang; Yifan Song; Ping Tian; Jiancun He; Yining Tan; Yutong Tian; Yele Sun; Zifa Wang (Urban Climate, 2025)

Urbanisation Affects Millipede Gut Microbiota Communities by Impeding Host Gene Flow - Hongyi Liu; Tangjun Xu; Wentao Ye; Yuanyuan Li; Ke He; Ying Zhu; Xiaoming Zou; Honghua Ruan (Molecular Ecology, 2025)
Urbanisation leads to the alteration of the living environment of soil fauna and isolates them, significantly influencing the evolutionary processes of soil fauna. Faunal gut microbiota serves to bridge hosts with changing environments; thus, they are viable indicators of host adaptation. For this study, we investigated how urbanisation affects the gut microbiota and population genetics of Spirobolus bungii . The results revealed that urbanisation did not affect the genetic diversity of S. bungii populations but acted as a barrier, which hindered its gene flow. Genetic differentiation was associated with the compositional similarity of gut microbiota among populations; however, environmental distinctions had no impact. Our findings highlighted that gene flow between populations was a critical factor, which supported the premise that urbanisation influences the gut microbiota compositions of species. This study contributes to a deeper understanding of the mechanisms that underlie changes in faunal gut microbiota driven by gene flow in the context of urbanisation.

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Erratum to: CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Generation of the 2022 earthquake swarm in intersection of four geological units in the seismic experimental Site, southwest China - Zhi Chen; Hongyi He; Kezhen Zuo; Xiaoxia Liu; Weiwei Wu; Zihan Gao; Zhaofei Liu; Maoliang Zhang; Lu-Lu Hao (Journal of Asian Earth Sciences, 2025)

Notably high salinity of geothermal water in the coastal area in Hainan Island, China, predominantly dominated by tectonic activities - Zhikeng Huang; Zhi Chen; Yang Liu; Chunguo Liu; Zheming Shi; Lei Liu; Zhaofei Liu; Hongyi He; Ying Li (Geothermics, 2025)

A novel biosensor for detecting V. parahaemolyticus based on cascade signal amplification of CRISPR/Cas14a and Exo III - Jiahong Wang; He Sun; Yuhan Gao; Shengjun Bu; Zebin Zhang; Chen Wang; Hongyi Zhang; Wenhui Zhang; Jiayu Wan (Food Control, 2025)

CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Tree mycorrhizal associations strongly mediate soil microbial β-diversity along an elevational gradient in a warm-temperate forest - Xinyue Wang; Yaru Wang; Yu Wang; Jieyan Yang; Hongyi He; Yuchen Ren; Chenlin Wang; Haibo Li; Xiongzhi Zhang; Huifang Zhang; Jingjing Wang; Xiuqing Yang; et al. (Applied Soil Ecology, 2025)

Applied experimental research on in-situ online monitoring instrument for soil radon in fault zone - Ying Zhao; Zhi Chen; Chengnan Wang; Xudong Hu; Zhaofei Liu; Hongyi He (Journal of Environmental Radioactivity, 2024)

Shale gas leakage and fault activation: Insight from the 2021 Luxian MS 6.0 earthquake, China - Zhaofei Liu; Zhi Chen; Ying Li; Zhidan Zhao; Shunying Hong; Le Hu; Ling Ma; Chang Lu; Yuanxin Zhao; Hongyi He; Shujuan Su; Ying Zhao; et al. (Tectonophysics, 2024)

Wall boundary conditions for RANS modelling of unidirectional and oscillatory boundary-layer flows - Hongyi Jiang; Liang Cheng; Fang He; Zhen Guo; Ye Cai; Zhenjin Cen; Lizhong Wang (Ocean Engineering, 2024)

Deep Underground Earthquake Observation: Small to Moderate Earthquakes and Microearthquakes Identification - Chang Chen; Wentao Wan; Yun Wang; Jingsong Liu; Hongyi Li; Qiangqiang Miao; Yongsheng He; Juan Qi; Chao Wang (Journal of Earth Science, 2024)

Crust uplift controls the massive emissions of 222Rn and CO2 in the Northeastern Tibetan Plateau, China - Zhaofei Liu; Zhi Chen; Ying Li; Zhidan Zhao; Anhui Sun; Jingchao Li; Jinyuan Dong; Ying Zhao; Le Hu; Zihan Gao; Chang Lu; Shujuan Su; et al. (Chemical Geology, 2024)

MCF-7 cell - derived exosomes were involved in protecting source cells from the damage caused by tributyltin chloride via transport function - Yiren Xiong; Guoqiang Guo; Hongyi Xian; Zuqing Hu; Di Ouyang; Jiayi He; Shanshan He; Renyi Liu; Zhenjie Gao; Meilin Tang; Ying Chen; Suqin Tan; et al. (Toxicology, 2024)

Effects of straw return on soil carbon sequestration, soil nutrients and rice yield of in acidic farmland soil of Southern China - Hongyi Li; Modian Xie; Bifeng Hu; Yin Zhou; Songchao Chen; Renbin He; Yuheng Li; Hongfen Teng; Wanru Zhao; Xiaolin Jia; Jie Peng; Hocine Bourennane; et al. (Environment, Development and Sustainability, 2024)

A flat lithosphere-asthenosphere boundary (∼60 km depth) in central Eastern China: Implications for lithospheric destruction and evolution - Xinfu Li; Xiaobo He; Shuo Xu; Hongyi Li; Guoming Jiang (Journal of Asian Earth Sciences, 2024)

Characteristics and main controlling factors of helium resources in the main petroliferous basins of the North China Craton - Zihan Gao; Zhi Chen; Hongyi He; Zhaofei Liu; Chang Lu; Hanyu Wang; Yili Luo; Ying Li (Acta Oceanologica Sinica, 2024)

Research progress of nanocellulose-based food packaging - Xiaotong Wang; Jing Guo; Hongyi Ren; Jing Jin; Hui He; Peng Jin; Zhengguo Wu; Yonghua Zheng (Trends in Food Science & Technology, 2024)

Macroevolution of avian T cell receptor C segments using genomic data - Chunhong Liang; Lin Sun; Ying Zhu; Ayong Zhao; Hongyi Liu; Ke He (Immunogenetics, 2023)

Spatio-temporal evolution of cropland ecosystem services value and its spatially varying dominate over the past two decades: A case study in Jiangxi Province in southern China - Bifeng Hu; Modian Xie; Renbin He; Zhou Shi; Yin Zhou; Hanjie Ni; Hongyi Li (Journal of Cleaner Production, 2023)

Temperature-responsive hydrogel prepared from carboxymethyl cellulose-stabilized N-vinylcaprolactam with potential for fertilizer delivery - Hongyi Shang; Xinxin Yang; He Liu (Carbohydrate Polymers, 2023)

Delineation and optimization of cotton farmland management zone based on time series of soil-crop properties at landscape scale in south Xinjiang, China - Nan Wang; Dongyun Xu; Jie Xue; Xianglin Zhang; Yongsheng Hong; Jie Peng; Hongyi Li; Abdul Mounem Mouazen; Yong He; Zhou Shi (Soil and Tillage Research, 2023)

Boston ivy-inspired natural-rich binder with strong adhesion for advanced silicon-based anodes - Xiangyu Lin; Yong Wen; Jie Wang; Hongyi Shang; He Liu; Xu Xu (Chemical Engineering Journal, 2023)

Identifying conservation priority zones and their driving factors regarding regional ecosystem services - Hongyi Li; Renbin He; Jie Hu; Yue Zhou; Modian Xie; Wanming Deng; Junjie Wang; Wanru Zhao; Shuangshuang Zhang; Yefeng Jiang; Zongzheng Liang; Lan Luo; et al. (Environment, Development and Sustainability, 2023)

Reduction mechanism of bamboo powder pyrolysis in selective lithium extraction from spent lithium-ion batteries - Xiaojian Liu; Yayun Ma; Xiangyang Zhou; Juan Yang; Hongyi Kang; Yuehui He; Jingjing Tang; Fanyun Su; Wan Yang; Yaguang Zhang (Journal of Environmental Chemical Engineering, 2023)

Climate and soil management factors control spatio-temporal variation of soil nutrients and soil organic matter in the farmland of Jiangxi Province in South China - Bifeng Hu; Modian Xie; Hongyi Li; Rebin He; Yue Zhou; Yefeng Jiang; Wenjun Ji; Jie Peng; Fang Xia; Zongzheng Liang; Wanming Deng; Junjie Wang; et al. (Journal of Soils and Sediments, 2023)

Gestational exposure to perfluoroalkyl substances is associated with placental DNA methylation and birth size - Hexing Wang; Wenyun Li; Jiaqi Yang; Yuanping Wang; Hongyi Du; Minghui Han; Linji Xu; Shuping Liu; Jianping Yi; Yue Chen; Qingwu Jiang; Gengsheng He (Science of The Total Environment, 2023)

Zircon U–Pb age constraints on the provenance and response to tectonics: Lower Oligocene of the western Qiongdongnan Basin, South China Sea - Yunliu Yang; Yunlong He; Xinong Xie; Shanshan Li; Licheng Cao; Daojun Zhang; Can Huang; Hongyi Xiao (Marine and Petroleum Geology, 2023)

Geochemical features of fluid in Xiaojiang fault zone, Southeastern Tibetan plateau: Implications for fault activity - Hongyi He; Zhi Chen; Zhaofei Liu; Zihan Gao; Le Hu; Chang Lu; Junjie Shao; Ying Li (Applied Geochemistry, 2023)

Polymorphism and varying selection within the MHC class I of four Anas species - Shidi Qin; Peter O. Dunn; Yang Yang; Hongyi Liu; Ke He (Immunogenetics, 2021)

Serum Bisphenol A, glucose homeostasis, and gestational diabetes mellitus in Chinese pregnant women: a prospective study - Jiaqi Yang; Hexing Wang; Hongyi Du; Linji Xu; Shuping Liu; Jianping Yi; Yue Chen; Qingwu Jiang; Gengsheng He (Environmental Science and Pollution Research, 2021)

Cladophora reblooming after half a century: effect of climate change-induced increases in the water level of the largest lake in Tibetan Plateau - Huan Zhu; Xiong Xiong; Hongyi Ao; Chenxi Wu; Yubang He; Zhengyu Hu; Guoxiang Liu (Environmental Science and Pollution Research, 2020)

Identification of a genomic region controlling thermotolerance at flowering in maize using a combination of whole genomic re-sequencing and bulked segregant analysis - Wei Zeng; Jian Shi; Chunhong Qiu; Yunhe Wang; Shamsur Rehman; Shuaishuai Yu; Shijie Huang; Chen He; Wanyi Wang; Hongyi Chen; Chen Chen; Chuanhong Wang; et al. (Theoretical and Applied Genetics, 2020)

Research Progress on the Toxic Antagonism of Selenium Against Mycotoxins - Zhihua Ren; Hongyi He; Yu Fan; Changhao Chen; Zhicai Zuo; Junliang Deng (Biological Trace Element Research, 2019)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

A study of heterosis, combining ability and heritability between two male sterile lines and ten inbred lines of Tagetes patula - Ye Ai; Qinghua Zhang; Chen Pan; Hongyi Zhang; Shuang Ma; Yanhong He; Manzhu Bao (Euphytica, 2015)

Redox potential and microbial functional gene diversity in wetland sediments under simulated warming conditions: implications for phosphorus mobilization - Zhijian Zhang; Hang Wang; Jizhong Zhou; Hongyi Li; Zhili He; Joy D. Van Nostrand; Zhaode Wang; Xinhua Xu (Hydrobiologia, 2015)

A Strategy for the Molecular Diagnosis in Hemophilia A in Chinese Population - Zhihui He; Juan Chen; Shiyan Xu; Shufen Chen; Xiao Xiao; Hongyi Li; Yibin Guo; Weiying Jiang (Cell Biochemistry and Biophysics, 2013)

Environmental significance of RSL in ancient city wall: historical desertification of Ordos Plateau, Northern China - Yinzhou Huang; Nai-ang Wang; Tonghui He; Hongyi Chen; Wenyong Feng; Hao Long (Climatic Change, 2009)

Fast method for the localisation of current dipoles in the human brain - Jun Li; Hongyi Zhu; Sailing He (Medical & Biological Engineering & Computing, 2001)